Medical Comorbidity in Alzheimer's Disease: A Nested Case-Control Study - Wang, Jen-Hung; Wu, Ya-Ju; Tee, Boon Lead; Lo, Raymond Y (Journal of Alzheimer's disease, 2018)
Little is known about the distribution of medical comorbidities in Alzheimer's disease (AD). We aimed to describe the comorbidity pattern of AD in a nested case-control study. Incident AD cases were identified by International Classification of Diseases codes in a random sample of 2 million individuals in Taiwan National Health Insurance program during 2001-2011. We further restricted cases to those treated with AD drugs of approved reimbursement. We sampled a set of age- and sex-matched control subjects (2:1 ratio) and employed conditional logistic regression to estimate the associations between pre-specified 14 comorbidities and AD. The clusters of multiple chronic diseases were then identified by exploratory factor analysis. A total of 2,618 AD cases were identified during 2001-2011 with a mean age of 76.1 years and female preponderance (59%). The most common 5 comorbidities in AD were hypertension (55.1%), osteoarthritis (38.2%), depression (32.3%), diabetes mellitus (DM) (25.7%), and cerebrovascular disease (CVD) (22.7%). After adjusting for age and sex, DM, osteoporosis, depression, and CVD were significantly associated with AD. The number of comorbidity was 3-fold greater in the AD group. The cluster of hypertension, DM, and hyperlipidemia was the most common combination in old age, whereas the cluster osteoarthritis and osteoporosis was the only multimorbidity pattern significantly associated with AD. Multimorbidity is common in AD. Depression, CVD, osteoporosis, and DM are associated with incident AD, supporting that their co-existence is a typical feature of AD at old age. Comorbidity care should be integrated into current management for patients with AD.